2020
DOI: 10.1371/journal.pone.0241174
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of differential expression profiles via transcriptome sequencing in SH-SY5Y cells infected with CV-A16

Abstract: Coxsackievirus A16 (CV-A16) is one of the viruses that is most frequently associated with hand-foot-and-mouth disease (HFMD). Previous studies have shown that CV-A16 infections are mostly self-limiting, but in recent years, it has been gradually found that CV-A16 infections can also induce neurological complications and eventually cause death in children with HFMD. Moreover, no curative drugs or preventative vaccines have been developed for CV-A16 infection. Therefore, it is particularly important to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Previous studies have reported that EV-A71, CVA16, and echovirus 30 can result in the differential expression of genes in the nervous system development pathways [ 21 , 24 , 25 , 26 ]. In this study, CVA6 infected 5-day-old ICR mice by intramuscular injection and human glioma (U251) cells, and differentially expressed genes (DEGs) were screened using RNA-seq analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that EV-A71, CVA16, and echovirus 30 can result in the differential expression of genes in the nervous system development pathways [ 21 , 24 , 25 , 26 ]. In this study, CVA6 infected 5-day-old ICR mice by intramuscular injection and human glioma (U251) cells, and differentially expressed genes (DEGs) were screened using RNA-seq analysis.…”
Section: Discussionmentioning
confidence: 99%